Perlindungan Pengetahuan Tradisional dan Ekspresi Budaya Berdasarkan Undang-Undang Pemajuan Kebudayaan - Sasqia Salsabilla (Jurnal Syntax Admiration, 2024)
The purpose of this study is to analyze by discussing the protection of cultural knowledge seen from Law No. 5 of 2017, which at the time of the case in decision 823/K/Pid.Sus/2009 occurred where Law No. 5 of 2017 had not been passed. Indonesian society is a communal society, where there is a lack of awareness in protecting traditional culture. The emergence of various problems related to the Protection of Intellectual Property in Traditional Knowledge and Cultural Expression has made the public begin to realize the importance of Intellectual Property Law itself. In this study, the researcher uses a normative juridical law research method, namely reviewing and studying literature, legislation related to Traditional Knowledge and Cultural Expression by conducting a Law and Literature approach by analyzing secondary data through literature such as books, journals, articles and laws and regulations related to Traditional Knowledge. As a result, Decision No. 823/K/Pid.Sus/2009 showed that judges lacked understanding of traditional knowledge, which at that time had not been specifically regulated and only through the Patent Law, Trademark Law, and Copyright Law. Public awareness of Intellectual Property Rights is also low, leading to legal uncertainty. Law No. 5 of 2017 provides protection for traditional cultural knowledge and expressions, such as arts and customs, with the state obliged to carry out inventory, maintenance, and preservation. This law also emphasizes the importance of public legal awareness in its enforcement.